Pendekatan Problem Posing Meningkatkan Kemampuan Pemahaman Konsep Dan Berpikir Kreatif Siswa SMA - Hifzi Meutia; Rini Sulastri (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
General purpose of this research is to get information about mastery of mathematics concept and improvement the ability of senior high school 11 in Banda Aceh student in creative thinking with Problem Posing model. Understanding the concept is the ability of students to repeat and link the concept that has been studied with the material being studied. Creative thinking is the ability to reason organically and evaluate the quality of a reason systematically. Problem Posing learning model is one form of cooperative learning model that emphasizes the participation and activities of students to find their own material (information) lessons to be learned through the materials available. This research was conducted in senior high school 11 in Banda Aceh especially class XII-IPA1 as experiment class and XII-IPA2 as sample class. The research type is experiment with quantitative approach. Instrument test in the form of a description of 4 questions with the highest value of 100 and the lowest 0. The instrument is used to determine the ability mastery of concepts and creative thinking of students. Before being used to test the students 'creative thinking ability in the implementation of the research, the test questions are tested to other schools to know the validity, reliability, power of the pretest and posttest. Technique data processing is analyzed with quantitative statistics tests students' creative thinking ability. For data processing researcher using SPSS 17.0. Normality test results can be seen the value of pretest class expression and control class sig. = 0.300; 0.120> 0.05 means both classes are normally distributed. Based on the calculation, the value of sig (2-tailed) = 0.002 / 2 = 0.001 shows that sig. (1-tailed) <0,05 so it can be concluded that the improvement of concept comprehension and creative thinking of experimental class students is better than improvement of student's creative thinking conventional class.